2013
DOI: 10.1017/jfm.2013.113
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent separation upstream of a forward-facing step

Abstract: The turbulent flow over a forward-facing step is studied using two-dimensional time-resolved particle image velocimetry. The structure and behaviour of the separation region in front of the step is investigated using conditional averages based on the area of reverse flow present. The relation between the position of the upstream separation and the two-dimensional shape of the separation region is presented. It is shown that when of ‘closed’ form, the separation region can become unstable resulting in the eject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 46 publications
10
77
0
Order By: Relevance
“…The same technique as Pearson et al (2013) was employed to determine the reattachment location in the wake of the cube, as well as the attachment location and intermittency on the top surface. Our particular application of this technique was to look for the first position where instantaneously U < 0 against the boundary while scanning from a downstream position towards an upstream position.…”
Section: Spatial Characteristics Of the Wakementioning
confidence: 99%
“…The same technique as Pearson et al (2013) was employed to determine the reattachment location in the wake of the cube, as well as the attachment location and intermittency on the top surface. Our particular application of this technique was to look for the first position where instantaneously U < 0 against the boundary while scanning from a downstream position towards an upstream position.…”
Section: Spatial Characteristics Of the Wakementioning
confidence: 99%
“…This technique generates a basis for modal decomposition of ensemble of instantaneous fluctuating velocity fields and provides the most efficient way of identifying the motions which, on average, contain a majority of the turbulent kinetic energy (TKE) in the flow. The energy contribution of the singular value across the modes, hence its shape, depends on the local spatial resolution of the data set, as discussed in Pearson et al (2013). This is because the energy content of each ith mode depends on the smallest resolved scale in the flow (i.e.…”
Section: Proper Orthogonal Decompositionmentioning
confidence: 99%
“…It remains unclear, however, if the two phenomena are driven by the same physical mechanism. Recently, Pearson et al [48] investigated the lowfrequency unsteadiness of the turbulent separation bubble upstream of a forward-facing step. They suggested that the fluctuation of the separated region is related to the convection of large turbulent structures in the incoming boundary layer.…”
Section: Comparison With Fixed-separation Flowsmentioning
confidence: 99%